Quadratic expressions

  • Created by: Kat
  • Created on: 19-05-13 15:18

Factorising quadratic expressions

  • Puts it back into its brackets
  • Form (x+p) (x+q) - p+q=a and pq=b
  • Once the quadractic expression has been factorised it can be used to solve the equation i.e. (x+2) (x+4) = 0 -- x=-2 or x=-4 
  • Always use the negative reciprocal of the number for the answer as shown above 

Completing the square

  • In an exam, they will either ask you to give your answer to a specified number or


No comments have yet been made